Effects of the implementation of open and distance learning (ODL) and open-ended laboratory (OEL) on water engineering laboratory / Nora Farina Mohd Halim, Doris Asmani Mat Yusof and Nur Muizzah Nawi - Mohd Halim, Nora Farina; Mat Yusof, Doris Asmani; Nawi, Nur Muizzah (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Due to the restriction of Movement Control Order (MCO), only limited essential services such as healthcare, logistics, food supply chain, and banking can operate while all schools and higher educational institutions were strictly closed. The enforcement from the government is to ensure that all Malaysians will stay at homes to stop the virus from spreading and breaking the chain of infection. On the first week of April, the Ministry of Higher Education announced that all higher learning institutions' teaching and learning sessions must be conducted online until December 31st. The aim of this study is to determine the effects of the implementation of Open and Distance Learning (ODL) and Open-Ended Laboratory (OEL) for Water Engineering laboratory. OEL is where students are given the freedom to develop their own experiments, instead of merely following the prepared set guidelines from a laboratory manual or elsewhere. The students must devise their own strategies and back them with explanations, theory and logical justification. Usually, the practice of OEL learning session is conducted by using face to face technique between students and lecturer. However, the normal practice of OEL learning session could not be implemented during MCO and the laboratory lesson is totally changed to online. From the analysis of this study, it is found that the percentage differences between ODL and OEL for CO1-PO4 is 10% while for CO2-PO6 is 13%. Therefore, it is proved that ODL is not the best method to measure the students' achievement based on their psychomotor skills.